Hotels as Noncongregate Emergency Shelters: An Analysis of Investments in Hotels as Emergency Shelter in King County, Washington During the COVID-19 Pandemic. Issue 6 (2nd November 2022) - Colburn, Gregg; Fyall, Rachel; McHugh, Christina; Moraras, Pear; Ewing, Victoria; Thompson, Samantha; Dean, Taquesha; Argodale, Sarah
Abstract: This study analyzes the COVID-19 homelessness response in King County, Washington, in which people were moved out of high-density emergency shelters into hotel rooms. This intervention was part of a regional effort to de-intensify the shelter system and limit the transmission of the virus to protect vulnerable individuals experiencing homelessness. This study used quantitative and qualitative methods to describe the experiences of and outcomes on individuals who were moved from shelters to noncongregate hotel settings. The study highlights a new approach to shelter delivery that not only responded to the public health imperatives of COVID-19, but also indicated positive health and social outcomes compared to traditional congregate settings. The findings establish an evidence base to help inform future strategic responses to homelessness as well as to contribute to the broader policy conversations on our nation's response to homelessness.